The Identity of Piety in the Digital Age (Study of the Use of Religious Symbols in Social Media) (Islamic Studies Journal for Social Transformation, 2019)
This article is a study of the use of religious symbols on social media that the authors associate with theconcept of religious identity. This study targets some dakwah content that has become a trend in social mediasuch as Facebook, WhatsApp and Twitter. The author uses a phenomenological approach as a basis forconducting social analysis, so that the phenomenon of the rise of the use of religious symbols on social mediacan be manifested well. The result of this study confirm about the indication of the use of religious symbolsas an imaging tool from among literalists. Some content also indicates the existence of economic motives inthe use of these symbols. I see the phenomenon is part of the symbolic expressions of certain groups inportraying their godly identity through social media
Keywords: Identity of Piety; Religious Symbols; Social Media.